Multipoint immobilization of papain via its inert centre offers an attune pH extractor: selective separation of CH3Hg+ from inorganic mercurials in aqueous admixtures using extractor's cystine residues - Tanay K. Mondal; Ankit Ghosh; Basudev Das; Tirtha Biswas; Biswajit Hansda; Shailja Mishra; Ancy Basumatary; Sambit Bandyopadhyay; Ilawanbet Tangsong; Chandana Kumari; Bhabatosh Mandal; Ashok K. Jha; et al. (Food Chemistry, 2026)

Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Time traveling through the floodscape: assessing the spatial and temporal probability of floods and susceptibility zones in the Lower Damodar Basin - Sambit Sheet; Monali Banerjee; Dayamoy Mandal; Debasis Ghosh (Environmental Monitoring and Assessment, 2024)

Does leaf wax isotopic characterisation of gymnosperms and angiosperms capture environmental gradients in Himalayas? - Deepak Kumar Jha; Pranav Hirave; Sambit Ghosh; Bibhasvata Dasgupta; Prasanta Sanyal (Organic Geochemistry, 2024)

First hand observations from the April 28, 2021 Sonitpur (MW 6.4) earthquake, Assam, India: possible mechanism involved in the occurrence of widespread ground effects - Mayank Joshi; Sambit Prasanajit Naik; Asmita Mohanty; Arun Bhadran; Drishya Girishbai; Swakangkha Ghosh (Geosciences Journal, 2023)

Flood characteristics and dynamics of sediment environment during Anthropocene: experience of the lower Damodar river, India - Debasis Ghosh; Sambit Sheet; Monali Banerjee; Manas Karmakar; Mrinal Mandal (Sustainable Water Resources Management, 2022)